Arctic plant-fungus interaction networks show major rewiring with environmental variation - Bastien Parisy; Niels M. Schmidt; Alyssa R. Cirtwill; Edith Villa-Galaviz; Mikko Tiusanen; Cornelya F. C. Klütsch; Paul E. Aspholm; Katrine Raundrup; Eero J. Vesterinen; Helena Wirta; Tomas Roslin (Communications Earth & Environment)
Abstract Global environmental change may lead to changes in community structure and in species interactions, ultimately changing ecosystem functioning. Focusing on spatial variation in fungus–plant interactions across the rapidly changing Arctic, we quantified variation in the identity of interaction partners. We then related interaction turnover to variation in the bioclimatic environment by combining network analyses with general dissimilarity modelling. Overall, we found species associations to be highly plastic, with major rewiring among interaction partners across variable environmental conditions. Of this turnover, a major part was attributed to specific environmental properties which are likely to change with progressing climate change. Our findings suggest that the current structure of plant-root associated interactions may be severely altered by rapidly advancing global warming. Nonetheless, flexibility in partner choice may contribute to the resilience of the system.